Modelando o emprego regional a partir do modelo GVAR: uma análise dos dados brasileiros - Athayde Junior, Mário Seganti (2016)
The goal of this work will be to contribute to the study of spatial econometric by using the concept of modeling for regional interdependence. Regional interdependence is a field of study whose research also has many fronts to explore. For the purpose of this work will be used the GVAR model (Global Vector AutoRegressive), proposed by Pesaran et al. The work will examine the application, to Brazilian data, of GVAR econometric concepts produced by German researchers on data of that country, and used in the paper 'Regional Unemployment Forecasts with Spatial Interdependencies', by Schanne, Wapler and Weyh (2008). The model GVAR used initially tests the existence of cointegration between the historic series of admission and dismissal of workers in 27 units (UF) of Brazil. Then, the model will be used as a tool for forecasting labor market occupancy rate. The results indicate that the existence of so-called 'dominant units' ends up playing a significant effect in terms of spatial econometrics, for the data used in this study.